POR UMA TEOLOGIA PROTESTANTE DAS RELIGIÕES Uma proposta teológica latino-americana em diálogo com a visão trinitária de Jürgen Moltmann - GONÇALVES, Alonso de Souza. (2020)
Given the absence of a more expressive theological concern from a Protestant perspective in Latin America with religious pluralism that could constitute a theology of religions, the main question we raise in this paper is: What are the paths for the construction of an ecumenical Protestant theology of religions in a Latin American perspective? This question is legitimate from the moment that there is a “near” absence of a Protestant theological concern in Latin America with religious pluralism and, as a consequence, the formulation of a theology of religions. We are aware that this “near” absence has its historical reasons, although Protestantism, with its ecumenical-progressive tendency and more social insertion in Latin America, was concerned with meeting the ecumenical demands of the churches. Because of this shortcoming, there was no more systematic and effective theological reflection on the theme in a Protestant environment. On the other hand, in the Catholic environment there is a broader production and reflection on the subject. Given this, and also the scarcity of Latin American Protestant authors who think about it, we chose to welcome the reflection of the German theologian Jürgen Moltmann, more specifically his conception of the trinity, in order to contribute to a Protestant theology of religions. Moltmann's theological reading of the trinity is permeated by a conception of openness and dialogicity. For the German theologian, the Trinitarian relationship is a relationship of equals, where there is no monarchy and hierarchy as a mode of relations between people. With this, it is possible the exchange between people, allowing the annulment of a subordinate relationship. This open relationship that is established between the persons of the trinity, from a metaphorical perspective, demonstrates the mode of coexistence, acceptance, relationship, equality. Thus, the thesis we are defending is that there are, from Jürgen Moltmann's theological conception of the trinity, elements that, once articulated with the theology of religions and with the Latin American context, would make it possible to formulate a proposal for a Latin American Ecumenical Protestant Theology of Religions. To pursue this proposal, we start from some questions: (i) what are the challenges that religious pluralism causes in Latin American theology? (ii) For what reasons did Latin American Protestantism not develop a theological reflection that took into account religious plurality and the fostering of a Theology of Religions? These first two questions suggest that there is a gap in Latin American Protestant theological reflection on the theology of religions. With this, we also ask: (iii) is there a possibility of having a proposal for Latin American Ecumenical Protestant Theology of Religions from Moltmann’s trinitarian reflection ?; (iv) if so, what contribution could a Latin American Ecumenical Protestant Theology of Religions make to interreligious dialogue in Latin America through pressing themes?